The Competitive Advantages of NURI East Java Savings and Loans Cooperatives and Sharia Financing in the Perspective of the Diamond Strategy - Nisa', Rifqun; Samsuri, Andriani (International Conference on Islamic Economic (ICIE), 2022)
This study aims to determine the application of competitive advantage to the NURI Sharia and Loans and Financing Cooperative (KSPPS NURI JATIM) in the diamond strategy prespective. The research methodology used is qualitative with a descriptive approach. Data collection was carried out by observation, documentation and interview methods. The data sources in this study were the Director of KSPPS NURI JATIM, administrators of KSPPS NURI JATIM, and members of KSPPS NURI JATIM. The research result obtained are KSPPS NURI JATIM’s competitive advantage in terms of marketing management, financial management, information management, and human resource management that have made efforts and are in accordance with ideal conditions. The potential of KSPPS NURI JATIM in the diamond strategy, KSPPS NURI JATIM must continue to improve service quality and expand marketing areas.